THE EFFECT OF GIVING MULTIPLE DOSES OF NPK FERTILIZER TABLET TO GROWTH AND PRODICTIN OF PINEAPLLE (Ananas comosus (L) Merr) IN PEATLAND - Mhd Al Irsyad Syah; Edison Anom; Sukemi Indra Saputra (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This study aimed to determine the effect of NPK fertilizer tablets Sigi and get the best dosage of pineapple crop production. Research has been conducted in the community garden Desa kualu Nenas Kampar District Riau Province began in February 2014 to June 2014. The study was carried out experiments using arandomized block design (RBD) consists of 4 treatments and 6 replications, each experimental unit consisted of 6 plant. The treatment given is without fertilizer NPK (P0), NPK fertilizer Sigi 1 tablet ( 11.869 g)(P1), NPK fertilizerSigi 2 tablets (23.738 g)(P2), NPK Sigi 3 tablets (35,607 g) (P3). Parametersmeasured were age at flowering, harvesting, fruit length, fruit circle, fruit weight, plot production. The results showed that NPK fertilizer tablets Sigi different effect on the production of pineapple plants. NPK fertilizer as much as 3 Tablets Tablets Sigi equivalent to a dose of 35.607 g / plant. The best effect on flowering plant age, time of harvest, fruit length, fruit circle, fruit weight, yield per plot on pineapple plant varieties queen. Keyword: pineapple, NPK tablet, production, peatland